Significant Bio-Ecological Parameters in Long Tailed Macaque (Macaca fascicularis) Business - Yanto Santosa (Department of Forest Resources Conservation and Ecotourism - IPB University, 1996)
Macaque (Macaca fascicularis) is one of a promising export commodities. To be aMe to maintain their preservation alld to reach an optimal and sustainable production level, there need to be captive breeding efforts. Significant information on the biology, ecology and population demographic parameters of these mscsques have been analyled from various literaturea and direct observations, in seven1 captive breeding sites.